2016
DOI: 10.5937/selsem1601017c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed priming on seed vigor and early seedling growth in maize under optimal and suboptimal temperature conditions

Abstract: Low temperature has a negative effect on germination parameters and early seedling growth. Seed priming is a beneficial pre-sowing treatment that partially hydrates the seeds to the point of germination process initiation, followed by drying which prevents radicle protrusion. The aim of this study was to evaluate the effect of different seed priming treatments on some maize seed vigor and early seedlings growth parameters at different temperature conditions. Seeds were primed in water (hydropriming) and KNO 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The root and shoot length were not significantly affected by mannitol priming. Similar result was obtained by Canak, et al [29] who reported that effects of priming treatments of maize seeds on root length were insignificant.…”
Section: Root and Shoot Length (Rl And Sl)supporting
confidence: 89%
“…The root and shoot length were not significantly affected by mannitol priming. Similar result was obtained by Canak, et al [29] who reported that effects of priming treatments of maize seeds on root length were insignificant.…”
Section: Root and Shoot Length (Rl And Sl)supporting
confidence: 89%
“…The positive effect of rice seed priming to is attributed to an increase in endospermic amylase activity resulting from the ameliorated soluble sugar content of the primed seed 4 . It is reported that seed priming could be used to achieve higher seed vigour and seedling growth in maize 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Pre-sowing seed priming is one such technology [27] that suggests that the yield gap in DSR compared to PTR caused by poor crop establishment can be closed with seed priming technology. Improved seed invigoration techniques, such as seed priming for its positive impacts including rapid and uniform crop establishment, early vigor, and yield gains, have been studied in various crops including mungbean [28], soybean [29], sorghum [30], wheat [31,32], and maize [33,34], and vegetables such as tomato [35]. Recently, with increased interest in transitioning from PTR to DSR, limited studies have been conducted on rice seed priming [36,37].…”
Section: Introductionmentioning
confidence: 99%